Factors affecting intention to subscribe SVOD in Vietnam - Lê, Phú Khánh (2020)
There is a lack of researchapplied UTAUT2 to understand consumer’s intention to subscribe to SVOD. Therefore, this thesis will test UTAUT2 in the SVOD context as empirical evidence contributesto the SVOD studies. The thesisalso teststhe role of Consumer Innovativeness and moderating effect of Media exposure to the UTAUT2 model to expand the approach of Media exposure as moderatorsand contribute to the theory of UTAUT2